La Crosse viral infection in hospitalized pediatric patients in Western North Carolina - Miller, Ansley; Carchman, Rebecca; Long, Rachel; Denslow, Sheri A (Hospital pediatrics, 2012)
La Crosse infection, caused by a rare mosquito-transmitted virus, is endemic in Western North Carolina. Given the large number of cases at our institution, our goal was to describe the presentation, management, and clinical course for pediatric patients with this disease. We retrospectively reviewed medical records from pediatric patients with antibody-confirmed La Crosse infection admitted to Mission Hospital July 2004 through August 2009. Demographics, clinical characteristics, management methods, length of hospital stay, and complications were analyzed. Regression analysis was used to assess relationships between presentation and clinical course. Forty-seven pediatric patients were identified with antibody-confirmed La Crosse infection. Seventy percent were male, and the median age was 8 years. Admission signs and symptoms included fever (43%), headache (94%), vomiting (78%), altered mental status (58%), and seizures (61%). All patients had pleocytosis on cerebrospinal fluid studies (range 10-1063 cells/mm3). Median length of stay was 5 days. Seizure at admission was associated with an increased length of stay (2.4 additional days, 95% confidence interval 0.7-4.1). Eighteen patients (38%) received intensive care, 7 (19%) received parenteral or enteral (via nasogastric tube) nutrition, and 4 (9%) received mechanical ventilation. No statistically significant associations between presenting signs and symptoms and complications were found. Treatments included antibiotics (87%), antiviral medication (55%), seizure prophylaxis (47%), and isotonic fluids (98%). Our data reflect few indicators to predict clinical course during hospital stay. Management strategies should include attention to development of seizure activity and preventive measures for syndrome of inappropriate antidiuretic hormone.